Mauritania : Anti-Corruption Study - World Bank (Washington, DC, 2013)
This report provides analytic support to the National Anti-corruption Strategy (NACS) formulation, offers lessons from international experience on governance and anti-corruption (GAC) policy, and generally supports the Government and its development partners to better understand the phenomenon of corruption in Mauritania. The report is structured as follows: Chapter 2 focuses on the definition and measurement of corruption and the Mauritanian political economy. Chapter 3 focuses on corruption in public procurement. Chapter 4 concentrates on corruption in the courts of law. Chapter 5 deals with the extractive industries. Chapter 6 focuses on corruption from the perspective of the private sector, based on the results of the recent Investment Climate Assessment (ICA). On the basis of the analysis conducted in this report, the single most important message concerns the need for maintaining momentum and pressing ahead with the finalization of ongoing anti-corruption strategic thinking and legislation, and the implementation of already approved GAC laws and measures. Looking forward, the emphasis should shift from passing laws and rules to concrete implementation of procedures on a broader agenda of greater political accountability. Priority areas include: (1) independence of the media, (2) monitoring procedures (such as a governance diagnostic survey) and (3) the establishment of an effective mechanism through which the voice of citizens and users of public services can be heard.